Molecular-driven assembled M-coated SiO2 hollow composite microspheres as well as preparation method and application thereof

Through molecularly driven assembly and sulfonic acid functional modification, M@SiO2 hollow composite microspheres with controllable size were prepared, which solved the problem of poor catalytic oxidation performance in the prior art and significantly improved the efficiency and stability of the catalytic oxidation reaction , suitable for catalyzing H2O2 photodegradation reactive dyes.

CN119318960AActive Publication Date: 2025-01-17ZHEJIANG UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411589338.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-17
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The preparation of hollow silica microspheres in the existing template method has problems such as shell damage, impurities introduction, uncontrolled size and poor catalytic performance, and it is difficult to show excellent performance in the field of catalytic oxidation.

Method used

Using acetylacetone metal salt and tetraethyl orthosilicate as raw materials, M@SiO2 hollow composite microspheres with controllable sizes are prepared by molecular-driven assembly method, and metal nanocluster formation is promoted through anionic surfactant and co-structure guide agent. Combined with sulfonic acid functional modification, the reaction site of the catalyst is improved.

Benefits of technology

The M@SiO2 hollow composite microsphere with a monodispersed structure and controllable size has been achieved, which significantly improves the catalytic oxidation performance and stability, and broadens the scope of application of catalysts, especially in catalytic H2O2 photodegradation reactive dyes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125150140000061
    Figure BDA0005125150140000061
  • Figure HDA0005125150150000011
    Figure HDA0005125150150000011
  • Figure HDA0005125150150000012
    Figure HDA0005125150150000012
Patent Text Reader

Abstract

The preparation method comprises the following steps: by taking acetylacetone metal salt as a core to be diffused to a hollow structure, taking an anionic surfactant as a template and taking tetraethoxysilane as a silicon source, carrying out hydrolysis and condensation reaction in a double-solvent solution, removing the template agent, and carrying out vacuum drying to obtain the M-coated SiO2 hollow composite microspheres. The monodisperse hollow mesoporous silica microspheres have the advantages of monodisperse structure, controllable size and the like; the high-stability, high-dispersion and cavity-size-adjustable mesoporous hollow silicon dioxide microsphere catalyst is prepared by taking acetylacetone salt as a metal source, and further through post-chlorosulfonic acid treatment, functional modification of the surfaces and internal pore channels of the silicon dioxide microspheres is realized, so that the mesoporous hollow silicon dioxide microsphere catalyst has an application prospect in the field of catalytic oxidation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a molecular driven assembly M@SiO 2 Hollow composite microspheres and a preparation method thereof, and applications in the field of catalytic oxidation. Background Art

[0002] Mesoporous hollow silica microsphere materials have shown great application potential in catalysis, separation, adsorption and controlled drug release due to their high specific surface area, high melting point, high stability and non-toxicity, and have therefore received widespread attention.

[0003] At present, the template method is the most commonly used method for preparing inorganic hollow microspheres. The size and dispersibility of the template material determine the size and size of the hollow silica microsphere cavity. The entire synthesis operation method is relatively simple. The template method is divided into hard template method and soft template method. The most commonly used hard template materials are polystyrene (PS) microspheres, silica spheres, inorganic salts, etc. Although the process is simple, there are still many shortcomings: (1) When removing the template, it is easy to destroy the shell structure and introduce impurities, which will also cause the deformation or collapse of the hollow microspheres; (2) The hydrolysis and condensation reaction of the silicon source on the template surface is difficult to balance and control; (3) It is difficult to control the integrity and uniformity of the silica layer coating on the template surface, and the reaction conditions need to be strictly controlled. Based on the above problems, the soft template method has been developed. Commonly used soft template agents include microemulsions, micelles, vesicles, and bubbles. For hollow mesoporous silica microspheres of different sizes, their performance varies greatly in applications such as catalysis, separation and controlled drug release. In addition, the controllable size of hollow silica microsphere materials can flexibly achieve controllable performance in practical applications, thereby expanding the scope of application and performance of the materials.

[0004] In view of this, the present invention uses acetylacetone metal salt as the metal source and tetraethyl orthosilicate as the silicon source, and controls the concentration of the raw material solution to drive the molecular assembly to prepare size-controllable M@SiO 2 Hollow composite microspheres and their application in catalytic oxidation reactions. Summary of the invention

[0005] The present invention aims to provide a molecular driven assembly of M@SiO 2 Hollow composite microspheres and preparation method and application thereof. The present invention can obtain M@SiO2 with a monodisperse structure and controllable size. 2 Hollow composite microspheres are provided, and their application in catalytic oxidation reactions is exemplified.

[0006] The technical solution of the present invention is as follows:

[0007] A molecule-driven assembly of M@SiO 2 A method for preparing hollow composite microspheres comprises:

[0008] Acetylacetone metal salt is dissolved in an organic solvent, and then a hydrochloric acid solution of an anionic surfactant, tetraethyl orthosilicate, and a co-structure directing agent are added, and the reaction is carried out at 50-130°C for 15-30 hours, and then cooled to room temperature, centrifuged, washed, and vacuum dried to obtain solid microspheres; the obtained solid microspheres are dispersed in an ethanolamine-ethanol solution, refluxed at 80-100°C for 10-20 hours, and then cooled to room temperature, centrifuged, washed, and vacuum dried to obtain M@SiO 2 Hollow composite microspheres;

[0009] in,

[0010] The metal element in the acetylacetone metal salt is one or two of Fe, Co and Ni;

[0011] The organic solvent is selected from one of ethanol, methanol and N,N-dimethylformamide;

[0012] The concentration of the solution obtained by dissolving the metal salt of acetylacetone in the organic solvent is 0.02-0.2 mol / L;

[0013] The anionic surfactant is selected from sodium N-lauroyl sarcosinate or sodium dodecyl hydrogen sulfate; the anionic surfactant not only acts as a template, but also promotes the formation of metal nanoclusters on SiO 2 Internal formation;

[0014] The hydrochloric acid solution of anionic surfactant is prepared by dissolving anionic surfactant in dilute hydrochloric acid (0.01 mol / L) (vigorously stirred for 1 to 2 hours), and the concentration of anionic surfactant is 20 to 50 mmol / L;

[0015] The co-structure directing agent is 3-aminopropyltriethoxysilane;

[0016] The molar ratio of acetylacetone metal salt, anionic surfactant, ethyl orthosilicate and co-structure directing agent is 2-20:4-20:100:5-10;

[0017] In the ethanolamine-ethanol solution, the concentration of ethanolamine is 0.001 to 0.005 mol / L;

[0018] The concentration of solid microspheres in the ethanolamine-ethanol solution is 5 to 10 g / L;

[0019] The washing may be performed using one or more of ethanol, methanol, and N,N-dimethylformamide, and the vacuum drying temperature is 80°C.

[0020] Furthermore, the M@SiO prepared by the above method 2 Hollow composite microspheres can be functionally modified. The specific modification methods are as follows:

[0021] M@SiO 2 The hollow composite microspheres were dispersed in dichloromethane, and a dichloromethane solution of chlorosulfonic acid was added dropwise under ultrasonication at room temperature for 20 to 60 minutes, followed by centrifugation, washing, and vacuum drying to obtain functionalized M@SiO 2 Hollow composite microspheres;

[0022] M@SiO 2 The concentration of hollow composite microspheres in dichloromethane is 20-50 g / L;

[0023] The concentration of chlorosulfonic acid in dichloromethane solution is 0.001-0.005 mol / L;

[0024] Chlorosulfonic acid and M@SiO 2 The feed ratio of hollow composite microspheres is 0.01-0.05:1, mmol / g;

[0025] The washing was carried out with dichloromethane and the vacuum drying temperature was 80°C.

[0026] Through post-chlorosulfonic acid treatment, not only can sulfonic acid groups be further grafted on the surface of the microspheres, but the surface of the silica can also be treated by chemical etching to expose the metal nanoparticles inside the microspheres. The exposure of the metal nanoparticles is significantly improved, which can provide more reaction sites and thus accelerate the catalytic reaction. Through this strategy, the overall performance of the catalyst can be effectively improved.

[0027] The present invention relates to M@SiO prepared by the above preparation method. 2 Hollow composite microspheres, functionalized M@SiO 2 Hollow composite microspheres.

[0028] The M@SiO 2 Hollow composite microspheres or functionalized M@SiO 2 Hollow composite microspheres have good catalytic oxidation performance and stability, and can be used as heterogeneous catalysts in the field of catalytic oxidation, for example: for catalytic H 2 O 2 Photodegradable reactive dyes.

[0029] The present invention has the following advantages:

[0030] 1. The size can be controlled to obtain hollow silica nanosphere materials with a size of 100 to 1200 nm, and the appropriate material and its synthesis method can be selected according to application requirements.

[0031] 2. Realize the functional modification of the surface and internal pores of hollow core-shell microspheres. Single metal or multi-metal M@SiO 2Hollow composite microsphere catalysts effectively broaden the scope of application of catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 : Mesoporous hollow Fe@SiO prepared in Example 2 of the present invention 2 TEM image of microspheres.

[0033] Figure 2 : Mesoporous hollow Fe@SiO prepared in Example 2 of the present invention 2 STEM and EDS images of microspheres.

[0034] Figure 3 : Fe@SiO prepared in Example 19 of the present invention 2 -SO 3 TEM electron microscope image of the shell pores of H microspheres.

[0035] Figure 4 : Mesoporous hollow Co / Fe@SiO prepared in Example 5 of the present invention 2 SEM electron microscope photos of microspheres. DETAILED DESCRIPTION

[0036] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0037] Embodiment 1:

[0038] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.01 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.01Fe@SiO 2 .

[0039] Embodiment 2:

[0040] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 .

[0041] Embodiment 3:

[0042] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.2 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated under reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.2Fe@SiO 2 .

[0043] Embodiment 4:

[0044] Cobalt acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50 ° C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80 ° C. Then, 0.5 g of the product was dispersed in 100 mL of a 0.001 mol / L ethanolamine-ethanol solution, heated to reflux at 80 ° C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: Co@SiO 2 .

[0045] Embodiment 5:

[0046] Nickel acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, which was recorded as: Ni@SiO 2 .

[0047] Embodiment 6:

[0048] Cobalt acetylacetonate and ferric acetylacetonate were dissolved in ethanol at a molar ratio of 1:1 to prepare a 100 mL metal organic solution with a metal ion concentration of 0.1 mol / L. 100 mL of 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution. 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added and reacted at 50 °C for 15 h. After the reaction was completed, centrifugation, washing, and vacuum drying at 80 °C were performed. Then, 0.5 g of the product was dispersed in 100 mL of ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 80 °C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: Co / Fe@SiO 2 .

[0049] Embodiment 7:

[0050] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 80°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -80.

[0051] Embodiment 8:

[0052] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 130°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -130.

[0053] Embodiment 9:

[0054] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 80°C for 30 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of a 0.001 mol / L ethanolamine-ethanol solution, heated to reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -80 / 30.

[0055] Embodiment 10:

[0056] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 80°C for 18 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -80 / 18.

[0057] Embodiment 11:

[0058] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 50 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -N50.

[0059] Embodiment 12:

[0060] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium dodecyl sulfate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of a 0.001 mol / L ethanolamine-ethanol solution, heated to reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -S20.

[0061] Embodiment 13:

[0062] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.005 mol / L, heated to reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -005.

[0063] Embodiment 14:

[0064] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 1.0 g of the product was dispersed in 100 mL of a 0.001 mol / L ethanolamine-ethanol solution, heated to reflux at 80°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -M10.

[0065] Embodiment 15:

[0066] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 90°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -R90.

[0067] Embodiment 16:

[0068] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 100°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -R100.

[0069] Embodiment 17:

[0070] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated under reflux at 100°C for 20 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -R100 / 20.

[0071] Embodiment 18:

[0072] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 0.223 mL of ethyl orthosilicate and 0.047 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50°C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80°C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 90°C for 10 h, centrifuged, washed, and vacuum dried to obtain a hollow composite microsphere heterogeneous catalyst, recorded as: 0.1Fe@SiO 2 -CR.

[0073] Embodiment 19:

[0074] Ferric acetylacetonate was dissolved in ethanol to prepare 100 mL of a metal organic solution with a concentration of 0.1 mol / L, and 100 mL of a 20 mmol / L sodium N-lauroylsarcosinate-hydrochloric acid solution was added to form a mixed solution, and then 2.23 mL of ethyl orthosilicate and 0.234 mL of 3-aminopropyltriethoxysilane were added, and the mixture was reacted at 50 ° C for 15 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum dried at 80 ° C. Then, 0.5 g of the product was dispersed in 100 mL of an ethanolamine-ethanol solution with a concentration of 0.001 mol / L, heated to reflux at 90 ° C for 10 h, centrifuged, washed, and vacuum dried to obtain Fe@SiO 2 Hollow composite microsphere heterogeneous catalyst. Further, 1g Fe@SiO 2 The hollow composite microspheres were dispersed in 40 mL of dichloromethane for functional modification. 10 mL of dichloromethane mixed solution containing 0.005 mol / L chlorosulfonic acid was added dropwise at room temperature under ultrasound. The reaction lasted for 30 min. After the reaction was completed, the mixture was centrifuged, the solid was washed, and vacuum dried to obtain sulfonated Fe@SiO2 Hollow composite microsphere heterogeneous catalyst.

[0075] Select typical M@SiO 2 (Example 2, Example 6 and Example 19) with SiO 2 The catalytic oxidation performance test was carried out to catalyze H 2 O 2 The experimental steps of photodegradation of reactive dyes are as follows: first, prepare 100 ml of 100 mg / L reactive brilliant red X-3B dye solution, adjust the pH of the reaction solution to 6.0 with dilute hydrochloric acid or sodium hydroxide; then weigh the catalyst and add it to the dye solution to make the concentration of the catalyst in the dye solution 0.1 g / L, disperse it ultrasonically, mix the catalyst and the solution evenly, and place it in a 30°C constant temperature oscillation box. Before the photocatalytic degradation experiment, oscillate the reaction solution in a dark environment for 30 minutes to achieve the adsorption equilibrium of the catalyst; place the light source above the solution, turn on the visible light lamp (the light source is a 150W sodium lamp), add H 2 O 2 The concentration was set to 2.12mmol / L, and the degradation experiment was started under visible light. The degradation time was 120min. During the oxidative degradation process, the reaction solution was drawn at certain time intervals for analysis and absorbance testing. The decolorization rate and metal leakage were calculated, and the results are shown in Table 1.

[0076] As shown in Table 1, hollow mesoporous SiO 2 The activity of the catalyst can be effectively improved after the microspheres are functionalized with sulfonic acid.

[0077] Table 1M@SiO 2 Comparison of performance of catalysts

[0078]

Claims

1. A method for preparing M@SiO2 hollow composite microspheres by molecular driven assembly, characterized in that: include: Acetylacetone metal salt is dissolved in an organic solvent, and then a hydrochloric acid solution of an anionic surfactant, tetraethyl orthosilicate, and a co-structure directing agent are added, and the mixture is reacted at 50-130°C for 15-30 hours, and then cooled to room temperature, centrifuged, washed, and vacuum dried to obtain solid microspheres; the obtained solid microspheres are dispersed in an ethanolamine-ethanol solution, refluxed at 80-100°C for 10-20 hours, and then cooled to room temperature, centrifuged, washed, and vacuum dried to obtain M@SiO2 hollow composite microspheres; in, The metal element in the acetylacetone metal salt is one or two of Fe, Co and Ni; The organic solvent is selected from one of ethanol, methanol and N,N-dimethylformamide; The anionic surfactant is selected from sodium N-lauroyl sarcosinate or sodium lauryl hydrogen sulfate; The co-structure directing agent is 3-aminopropyltriethoxysilane.

2. The method for preparing the molecularly driven assembled M@SiO2 hollow composite microspheres according to claim 1, characterized in that: The concentration of the solution obtained by dissolving the acetylacetone metal salt in the organic solvent is 0.02-0.2 mol / L.

3. The method for preparing the molecularly driven assembled M@SiO2 hollow composite microspheres according to claim 1, characterized in that: The hydrochloric acid solution of anionic surfactant is prepared by dissolving anionic surfactant in 0.01 mol / L dilute hydrochloric acid, and the concentration of anionic surfactant is 20-50 mmol / L.

4. The method for preparing the molecularly driven assembled M@SiO2 hollow composite microspheres according to claim 1, characterized in that: The molar ratio of acetylacetone metal salt, anionic surfactant, ethyl orthosilicate and co-structure directing agent is 2-20:4-20:100:5-10.

5. The method for preparing the molecularly driven assembled M@SiO2 hollow composite microspheres according to claim 1, characterized in that: In the ethanolamine-ethanol solution, the concentration of ethanolamine is 0.001 to 0.005 mol / L.

6. The method for preparing the molecularly driven assembled M@SiO2 hollow composite microspheres according to claim 1, characterized in that: The concentration of the solid microspheres in the ethanolamine-ethanol solution is 5-10 g / L.

7. The molecule-driven assembled M@SiO2 hollow composite microspheres prepared by the preparation method according to any one of claims 1 to 6.

8. A functionalized M@SiO2 hollow composite microsphere obtained by functionalizing and modifying the M@SiO2 hollow composite microsphere assembled by molecule drive according to claim 7, wherein the modification method is as follows: The M@SiO2 hollow composite microspheres were dispersed in dichloromethane, and a dichloromethane solution of chlorosulfonic acid was added dropwise at room temperature while ultrasonicating for 20 to 60 minutes, followed by centrifugation, washing, and vacuum drying to obtain functionalized M@SiO2 hollow composite microspheres. The concentration of M@SiO2 hollow composite microspheres in dichloromethane is 20-50 g / L; The concentration of chlorosulfonic acid in dichloromethane solution is 0.001-0.005 mol / L; The feed ratio of chlorosulfonic acid to M@SiO2 hollow composite microspheres is 0.01-0.05:1, mmol / g.

9. Use of the molecularly driven assembled M@SiO2 hollow composite microspheres as claimed in claim 7, or the functionalized M@SiO2 hollow composite microspheres as claimed in claim 8 as heterogeneous catalysts in the field of catalytic oxidation.

10. The use according to claim 9, characterized in that Used to catalyze H2O2 photodegradation of reactive dyes.

Citation Information

Patent Citations

  • Method for preparing silicon dioxide mesoporous hollow sphere material of polyhedral internal morphology

    CN102101673A

  • One-step synthesizing method for hollow type multilevel-hole Fe-Silicalite-1

    CN104098106A

  • Sulfonic functionalized mesoporous silicon dioxide microsphere loaded metal oxide catalyst and preparation method and application of catalyst

    CN104646033A

  • Polymerized microcrystalline catalyst for encapsulating Cu and Fe oxides, preparation method and application thereof

    CN112547134A

  • Double-metal-element-doped silicon dioxide composite nanomaterial as well as preparation method and application thereof

    CN115957762A